2013
DOI: 10.1053/j.ajkd.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Care Among Medicare Beneficiaries With ESRD: Medicare Consumer Assessment of Healthcare Providers and Systems (CAHPS) Survey Results

Abstract: On average, beneficiaries with ESRD report patient experiences that are at least as positive as non-ESRD beneficiaries. However, black and less educated patients with ESRD reported worse experiences than other ESRD patients. Stratified reporting of patient experience by race/ethnicity or education in patients with ESRD can be used to monitor this disparity. Physician choice and confidence and trust in physicians may be particularly important for patients with ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…This is consistent with findings from research showing that patients with diabetes in the U.S. generally report a more positive experience of care than those without diabetes (22). However, we also found important evidence of differences in the primary care experiences for diabetes patients with comorbid conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with findings from research showing that patients with diabetes in the U.S. generally report a more positive experience of care than those without diabetes (22). However, we also found important evidence of differences in the primary care experiences for diabetes patients with comorbid conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Our study builds on what is known within a U.S. context about health care experiences among people with diabetes (28) and those with complications often arising from diabetes (22) by investigating the experience of people with diabetes in a U.K. setting in which a national health system with universal coverage enables access to free healthcare for all residents. Particular strengths of our study are the large sample size, our analysis of the impact of comorbidity, and our ability to investigate how the experiences of people with diabetes vary by sociodemographic characteristics and health status.…”
Section: Primary Care Experiences Among People With Diabetes Vary By mentioning
confidence: 99%
“…An evaluation of the CAHPS Medicare survey for patients with ESRD conducted in 2009-2010 was recently reported (12). The cohort included 3794 patients with ESRD drawn from a database of 823,564 Medicare beneficiaries.…”
Section: Discussionmentioning
confidence: 99%
“…Mean response rates to recent CAHPS surveys ranged from 34 % to 61 %. 4,22 A metaanalysis of studies of nonresponse bias found no consistent relationship between a survey's nonresponse rate and nonresponse bias. 23 Nevertheless, it is important to be aware of the possibility of bias and use available information to adjust results so that nonresponse does not result in biased comparisons.…”
Section: Patient Experience Scores May Be Confounded By Factorsmentioning
confidence: 99%